Design and Implementation of Emulation and Verification Platform for Urban Rail Transit FAO System - LU Xiangyang; CHEN Huaguo; LEI Chengjian; LIAO Yun; ZHOU Kaicheng (Kongzhi Yu Xinxi Jishu)
To overcome the problems of high cost, low efficiency and long time period of on-site test and commissioning process for fully automatic operation(FAO) of urban rail transit, a design of emulation and verification platform for FAO was proposed. System structure of the emulation platform for FAO system was designed, and key technical issues of building the platform was pointed out such as interface management, emulation management, virtual train, virtual station, and signalling system virtual environment , and solution of these key issues was presented. Testing and verification ability of the functionality of various FAO scenes and the performances of the related scenes were shown by the emulation platform primary built according to the design. Application of the emulation platform was prospected.